Learning Islam from Da’i Mualaf: From Curiosity to Strengthen Religious Identity - Stepanus Sigit Pranoto (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This article is part of a study on religious discourse in the new media era. The main study discussed here is how the public access to da’wah content on social media delivered by da’i mualaf. Using a virtual ethnography method, this research studies and analyzes some da’wah content on the YouTube social media platform. The results of this study show that there are a variety of people’s motivations in accessing da’wah content, including curiosity about the story of the conversion of the da’i mualaf, which in turn affirms their religious identity as a Muslim. This research also showed a variety of public expression shown in a variety of comments, among other support, criticism, and even theological debate